2009
DOI: 10.1007/s11814-009-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the influence of over fire air position on the combustion in a single furnace boiler with dual circle firing

Abstract: The Computational fluid dynamics (CFD) code PHOENICS is applied to simulate and evaluate the combustion process within the furnace of a 1,000 MW dual circle tangential firing single furnace lignite-fired ultra supercritical (USC) boiler. The dependence on overfire air (OFA) positioning on the combustion process is studied. The results show that the highest temperature appears on the upside of the burner zone close to the front wall, and the high temperature zone rises with elevated OFA positions. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Fan et al 10,11 and Zhang et al 12 experimentally investigated the influence of air stoichiometric ratio and OFA port position on NO x emission for bituminous coal in an electrically heated one-dimensional furnace and a 3 MW pilot scale facility, respectively. Huang et al, 13 Liu et al, 14 and Zhou et al 15 numerically studied the effect of various OFA parameters on the NO x emission. Wu et al 16 found that NO x emission could be reduced by about 50% when the OFA ratio raised from 25% to 30% for a 600 MW wall fired furnace fed with bituminous coal.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al 10,11 and Zhang et al 12 experimentally investigated the influence of air stoichiometric ratio and OFA port position on NO x emission for bituminous coal in an electrically heated one-dimensional furnace and a 3 MW pilot scale facility, respectively. Huang et al, 13 Liu et al, 14 and Zhou et al 15 numerically studied the effect of various OFA parameters on the NO x emission. Wu et al 16 found that NO x emission could be reduced by about 50% when the OFA ratio raised from 25% to 30% for a 600 MW wall fired furnace fed with bituminous coal.…”
Section: Introductionmentioning
confidence: 99%
“…Tangentially fired pulverized-coal boilers have been widely used in industrial power generation, especially in China . Dual-circle tangential-firing single-furnace systems are employed in large-capacity boilers, with the benefits of steady combustion and uniform temperature distribution. , …”
Section: Introductionmentioning
confidence: 99%
“…Many numerical investigations have been reported on flow, combustion, heat transfer, and pollutant formation in coal-fired boilers. These studies focus on the combustion process, temperature deviation, and NO x emissions. One of the efficient methods to reduce the NO x emissions during the combustion process is the employment of OFA. , Under the OFA operation, the temperature of the burner zone will be reduced and NO x can be changed to N 2 in the fuel-rich region in the furnace. , Liu et al investigated the influence of the OFA position on the NO x emissions. They found that the NO x emissions can be greatly reduced with less influence on combustion efficiency by adjusting the OFA position.…”
Section: Introductionmentioning
confidence: 99%
“…These large-scale boilers typically employ either over fire air (OFA) or separating OFA processes [2][3][4][5] so as to reduce the generation of NO x [2,[5][6][7][8][9][10][11][12]. The temperatures of the main and reheat steam in a 1000 MW ultra-supercritical boiler can reach 605 C and 603 C, respectively, and thus approach the upper temperature limits of the metallic materials from which the boiler is made.…”
Section: Introductionmentioning
confidence: 99%